Fruit and vegetable growers irrigation survey - Sutcliffe, Chloe (Cranfield University, 2021)
This dataset provides the results of an online qualtrics survey investigating irrigation practice and perspectives on resilience to water risks amongst UK fruit and vegetable growers. The survey was live between January and April 2018.
Keywords: irrigation'; 'UK'; 'fruit and vegetables'; 'resilience'; 'water risks'; 'Agricultural Hydrology (Drainage; Flooding; Irrigation; Quality; etc.)'; 'Farming Systems Research'